Respuesta :

Answer:

Step-by-step explanation:

first we need to find the slope using the slope formula :

slope = (y2 - y1) / (x2 - x1)

(-9,7)...x1 = -9 and y1 = 7

(-6,-3)....x2 = -6 and y2 = -3

now we sub

slope = (-3 - 7) / (-6 - (-9) = -10 / (-6 + 9) = -10 / 3

so our slope is -10/3

now we use y = mx + b....with m representing the slope

slope(m) = -10/3

use either of ur points....I will use (-9,7)...x = -9 and y = 7

we are solving for b, the y intercept

now we sub

7 = -10/3(-9) + b

7 = 30 + b

7 - 30 = b

- 23 = b

so ur equation is : y = -10/3x - 23